Turkish SMEs' use of financial statements for decision making - Howard E. VanAuken; Semra Ascigil; Shawn Carraher (The Journal of Entrepreneurial Finance (JEF), 2017)
With a sample of 91 small Turkish firms, this study examines the factors that affect the use of financial statements, and the important information they contain, to make decisions. A principal components analysis identifies three key variables that determine the use of financial statements: experience, confidence, and knowledge. Logit analysis reveals that these three variables are significantly associated with whether Turkish business owners use financial statements to make decisions. These results can help business owners and service providers for these businesses understand what affects their use of financial statements and the process by which financial statements get incorporated into decisions.
Keywords: 650; Finance; International; Financial Statements